Vegetation Structure and Diversity Analysis in the Manigam Block of Lidder Forest Division of Kashmir - Akhter, Amreena; Bhat, G. M.; Khan, Parvez Ahmad; Dutt, Vaishnu; Mugloo, J. A.; Jeelani, M. Iqbal; Bakshi, Megna Rashid; Rather, Khalid ul Islam; Jan, Humaira (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during April, 2022–August, 2024 at block Manigam of Lidder Forest Division, Anantnag district, Jammu & Kashmir, India to investigate the differences in plant and tree species diversity and community structure. Vegetation sampling was done by the quadrat method, and quadrates were laid down by systematic random sampling methods along the four vertical transects which were 100 m apart. In each transect, quadrates were laid down at definite intervals. The findings showed that a total of 29 plant species from 23 families were found at these four distinct elevations. Of the 29 plant species that were documented, 9 were shrubs from 7 families and 4 were trees, representing 3 families. There were 16 herbaceous species, belonging to 13 families. The main tree at all four elevations was Pinus wallichiana, which had IVI values of 155.4, 156.33, 158.42, and 182.61, respectively. At altitude 1, Parrotia jacquemontiana dominated the shrub population with an IVI score of 83.83. Rosa rubiginosa was prevalent at altitudes three and four, with IVI values of 64.98 and 67.26, respectively, whereas Sambucus wightiana was dominating at altitude two, with an IVI value of 56.56. Among herbs, taraxacum officinale with IVI value of 58.84 was dominant at altitude 1st. Fragaria vesca was dominant at altitude 2nd and 3rd with IVI values of 44.93 and 72.06, respectively. Iris hookeriana with IVI value of 112.69 was dominant at altitude 4th. Out of four altitudes, altitude 2nd reported the highest number of species followed by 1st, 3rd and 4th, respectively.